Influence of two additives on the productive and sanitary response of growth-fattening pigs. (2017)
This work aimed to study the influence of two additives (microbial preparation and antibiotic growth promoter) on the productive and sanitary response of pigs in growth-feed. 120 castrated pigs of 71 days and 28.62 kg were used; they were distributed in three groups according to a completely randomized design with four replications each. The treatments (T) were: T1, without additive; T2, concentrated plus 1.0 and 0.5 kg of 2% virginiamycin per ton of feed for growing and fattening pigs, respectively; T3, concentrated plus 15 mL of the microbial preparation per kg of body weight (BW) of the animal.The preparation contained 4x106 CFU / ml of lactic acid bacteria and 1.5x105 CFU / mL of yeast. The animals treated with T3 had the highest final weight (98.41 kg, P <0.0001) and the best gain of total weight (69.84 kg; P <0.0001) and daily gain (712.50 g / d, P <0.0001). The most efficient conversion of dry matter (3.04 kykg BW), crude protein (551.63 g/kg BW) and metabolizable energy (41.80 MJ/kg BW) was found in the same group. The incidence of diarrhea was lower in the groups treated with the additives, with no difference between them. It is concluded that the additives improve the productive and sanitary performance of pigs in growth-feed stage, and this effect was greater with the microbial preparation.